Application of "omics" to Prion Biomarker Discovery. (4th March 2010) - Huzarewich, Rhiannon L. C. H.; Siemens, Christine G.; Booth, Stephanie A.
Abstract : The advent of genomics and proteomics has been a catalyst for the discovery of biomarkers able to discriminate biological processes such as the pathogenesis of complex diseases. Prompt detection of prion diseases is particularly desirable given their transmissibility, which is responsible for a number of human health risks stemming from exogenous sources of prion protein. Diagnosis relies on the ability to detect the biomarker PrP Sc, a pathological isoform of the host protein PrP C, which is an essential component of the infectious prion. Immunochemical detection of PrP Sc is specific and sensitive enough for antemortem testing of brain tissue, however, this is not the case in accessible biological fluids or for the detection of recently identified novel prions with unique biochemical properties. A complementary approach to the detection of PrP Sc itself is to identify alternative, "surrogate" gene or protein biomarkers indicative of disease. Biomarkers are also useful to track the progress of disease, especially important in the assessment of therapies, or to identify individuals "at risk". In this review we provide perspective on current progress and pitfalls in the use of "omics" technologies to screen body fluids and tissues for biomarker discovery in prion diseases.